2010
DOI: 10.1016/j.jcrs.2009.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the riboflavin film in corneal collagen crosslinking

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 24 publications
(44 reference statements)
3
120
0
7
Order By: Relevance
“…Wollensak et al 19 reported that dextranriboflavin solution used in the standard CXL procedure forms a stable 70-mm pre-corneal film after 1 min and had a breakup time of 22 min in human donor corneas, which reduced the UVA irradiance in stroma at a depth of 400 mm from 0.68 to 0.21 mW/cm 2 to shield the corneal endothelium from UVA. Steeper corneal curvatures could thus lead to a thinner pre-corneal riboflavindextran pre-corneal film and reduced shielding of the corneal endothelium and the thresholds for toxicity to be exceeded.…”
Section: Uva Radiation Delivered To Surface At Differentmentioning
confidence: 99%
“…Wollensak et al 19 reported that dextranriboflavin solution used in the standard CXL procedure forms a stable 70-mm pre-corneal film after 1 min and had a breakup time of 22 min in human donor corneas, which reduced the UVA irradiance in stroma at a depth of 400 mm from 0.68 to 0.21 mW/cm 2 to shield the corneal endothelium from UVA. Steeper corneal curvatures could thus lead to a thinner pre-corneal riboflavindextran pre-corneal film and reduced shielding of the corneal endothelium and the thresholds for toxicity to be exceeded.…”
Section: Uva Radiation Delivered To Surface At Differentmentioning
confidence: 99%
“…The complete removal of the epithelium has been recommended as an initial step of the CXL procedure since its lipophilic nature reduces the diffusion of riboflavin into the corneal stroma (20)(21)(22)(23)(24)(25)(26) . Moreover, the epithelium may block UV rays (27)(28)(29) .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that riboflavin is essential to CXL process, not only by acting as a photosensitizer, but also by preventing the harmful effects of irradiation (20,22,23) . This drug absorbs UVA preventing injuries to deeper ocular structures such as the endothelium, crystalline lens and retina.…”
Section: A B C D E Fmentioning
confidence: 99%
“…показано, что повышение концентрации рибофлавина в строме обратно пропор-ционально степени связывания фибрилл коллагена [18]. При этом роговицу с рибофлавином следует рассматри-вать как двухсоставную систему: строма-рибофлавин и прекорнеальная рибофлавиновая пленка, которая явля-ется неотъемлемой частью процедуры кросслинкинга и играет важную роль в достижении дозирования УФ-А-излучения [19].…”
Section: механизм уф-кросслинкингаunclassified